A tale of two Eberts: Videogames and the arbitrariness of meaning - Kaczmarski, Paweł (Replay. The Polish Journal of Game Studies, 2022)
The article revisits and examines in detail the so-called Ebert debate: an exchange of polemic voices between Roger Ebert, his opponents and supporters, on the issue of the relationship – both actual and potential – between games and works of art. Initiated by Ebert’s famous remarks that games can never be art, the debate offers a variety of views on the nature of art, the role of experience in art and games, the possibility of artistic expression in games, and the autonomy of art. The main point of the article is not so much to compare these views as to explain the contradiction at the heart of Ebert’s own argument: the critic seems to be constantly torn between the idea that games cannot be art in principle and the more practical view that it is impossible to know for certain that no games will ever become art. This contradiction seems to stem directly from Ebert’s inconsistent views as to the source of meaning in games, and it allows us to shed new light both on the nature of games as a medium, and on fundamental issues with contemporary games studies/criticism.